Community Development In Coastal Society Based on Islamic Values Perspective In Tanjung Village, Pademawu, Pamekasan - Trisnawati Saleh (Karsa: Journal of Social and Islamic Culture, 2017)
Empowering communities in Tanjung region shows a reflection of the manifestations of Islamic values that appear on the socio-economic life of society. Directly or indirectly characteristics appear in the civility of society both in the association that is civilized, personal piety and social piety. Empirically also happens strengthening the spiritual sphere through strengthening institutions such religious Al-Azhar Mosque, Al-Qur’an education program (TPQ) Nurul Huda, Pengajian Rutinan (spiritual dimension); strengthening institutions, especially in the field of education both formal and non-formal form of pre-school (TK) Harapan, early childhood education (PAUD) Bina Harapan, smart-house (Rumah  Pintar)  and library (Perpustakaan Harapan)  and coastal environmental education (intellectual dimension); and there was a strengthening in economic evident from the emergence of entrepreneurship programs through Family Empowerment Station (Posdaya) Harapan Mandiri and cadre empowering (economic dimension).Copyright (c) 2017 by KARSA. All right reserved DOI: 10.19105/karsa.v25i1.1028